Spatial–temporal trends and economic losses associated with bovine abortifacients in central Argentina - Canton, German Jose; Moreno, Fabiana Carina; Fiorentino, María Andrea; Hecker, Yanina; Spetter, Lucas Maximiliano; Fiorani, Franco; Monterubbianesi, María Gloria; Garcia, Juan Angel; González Altamiranda, Erika; Cirone, Karina Mariela; Louge Uriarte, Enrique Leopoldo; Verna, Andrea Elizabeth; et al. (Springer, 2022)
The aims of this work are, firstly, to provide the geolocalization of cases of bovine abortion with definitive diagnosis and, secondly, to estimate the economic losses due to the most frequent abortifacients diagnosed agents in cattle in Buenos Aires province, Argentina. The total beef and dairy cattle population at risk of abortion is 8,358,186 and 538,076, respectively. In beef cattle, the overall risk of abortion was estimated at 4.5% for all pregnancies, where 27.9% are due to Campylobacter fetus, Neospora caninum, Leptospira spp., Brucella abortus, and bovine viral diarrhea virus with economic losses of US$ 440 per abortion, being the annual loss to the beef industry of US$ 50,144,101. In dairy cattle, there was an 8.0% risk of suffering abortion, 26.1% produced by the same abortigenic agents. The economic losses were estimated at US$ 1,415 per abortion, which equals a total loss of US$ 17,298,498 for the dairy industry in the region. The results of this study show that infectious causes are highly prevalent in Buenos Aires province, and they caused severe economic impacts in the dairy and beef industries. Furthermore, changes in temporal trends of infectious abortion occurrence were detected, probably related to the inclusion of molecular diagnostic techniques with more sensitivity or different epidemiological or husbandry conditions in the region analyzed.